Pott’s puffy tumour secondary to frontal sinusitis - Mohamad, Adam; Leman, Wan Ishlah; Asha'ari, Zamzil Amin; Mohamad, Irfan (Polish Society of Family Medicine, 2018)
Frontal sinusitis is a common encounter in otorhinolaryngology practice. Most patients will present with frontal headache which worsens on bending forward, reduced sense of smell and sometimes cacosmia. Pott’s puffy tumour is an osteomyelitis of the frontal bone, which was originally described as a result of trauma, but it can also develop as a result of frontal sinusitis. We present a rare case of a rapidly progressing Pott’s puffy tumour involving the frontal sinus. The oedema subsided after antibiotic treatment and the patient underwent functional endoscopic sinus surgery.